In vitro and in vivo biological behavior of CDHA/OCP/β-TCP scaffold - Minarelli-Gaspar, A. M. [UNESP]; Saska, S. [UNESP]; Jimenez, J.; da Cunha, L. R. [UNESP]; Bolini, Paulo Domingos André [UNESP]; Leal, C.; Morejon-Alonso, L.; Carrodeguas, R. G.; Lopez-Bravo, A.; Zavaglia, C. A. C. (Trans Tech Publications Ltd, 2008)
The biological behavior of a new bioactive material composed of calcium-deficient hydroxyapatite, octacalcium phosphate, and beta-tricalcium phosphate was investigated by in vitro indirect and direct cytotoxicity, cell adhesion and proliferation tests, and by in vivo subcutaneous and bone implantation in rats. The results of the in vitro studies showed that the material is biocompatible and no cytotoxic. Slightly poorer initial cell adhesion and lower cell proliferation than in control was observed, which were attributed to the reactivity and roughness of the material surface, In vivo results showed that the material is biodegradable and bioactive in bone tissue, but only biocompatible and partially biodegradable in soft tissue.
Keywords: β-tricalcium phosphate; Calcium deficient hydroxiapatite; In vitro; In vivo; Octacalcium phosphate; Bioactivity; Bone; Calcium phosphate; Cell proliferation; Cytotoxicity; Hydroxyapatite; Biomaterials